Peru’s adaptation to the rise of China in the early 21st century: Between pragmatism and acquiescence - Ramírez Bullón, Javier Ernesto (2021)
This paper seeks to describe and explain the character of Peruvian foreign policy towards China during the early 21st century. From a historical perspective focused on the role of internal factors, the analysis identifies the main governmental and nonstate actors that shape the China-Peru relation in three key dimensions: political/diplomatic, economic/ commercial, and military/strategic. Furthermore, shows how these aspects interrelate each other to shape the structure and the political process behind the adaptation of Peru to the rise of China. The study ends with some final thoughts on the benefits and vulnerabilities of maintaining a pragmatic approach to China. In this sense, the findings recognizes that one of the virtues of pragmatism is the construction of a flexible foreign policy, capable of diversify alliances with multiple great powers. However, the analysis also warns of the need to understand how the national interests of Peru are constructed vis-à-vis China, since the pragmatic proximity can hide an acquiescent international attitude.